The Association between Serum Lipid Profile and Nephropathy in Type 2 Diabetes Mellitus Patients (Academia Journal of Medicine, 2019)
Background: The prevalence of hypercholesterolemia (TC>200md/dl) alone, as reported tin numerous studies across India, has varied from  about 20% to 35%. However, what is more important is the pattern of dyslipidemia. When compared with the western populations, Indians and  migrant Asian Indians tend to have higher triglycriede levels and lower HDL-C levels. Subjects and Methods: This was a comparative study  conducted among 100 cases. A pre-structural proforma will be used to collect baseline date detailed clinical history with clinical examination  and relevant investigation will be done on participating individuals. Results: There was correlation between lipid levels and duration of  diabetes for all lipid fractions which were significant. Conclusion: Correlation coefficient between nephropathy and lipid profile was found to  be significant.
Keywords: Hypercholesterolemia; Nephropathy and Lipid Profile